Automated detection and classification of multi-cell Phytoliths using Deep Learning-Based Algorithms - Berganzo-Besga, Iban; Orengo, Hector A.; Lumbreras, Felipe; Aliende, Paloma; Ramsey, Monica N. (Journal of archaeological science, 2022)
This paper presents an algorithm for automated detection and classification of multi-cell phytoliths, one of the major components of many archaeological and paleoenvironmental deposits. This identification, based on phytolith wave pattern, is made using a pretrained VGG19 deep learning model. This approach has been tested in three key phytolith genera for the study of agricultural origins in Near East archaeology: Avena, Hordeum and Triticum. Also, this classification has been validated at species-level using Triticum boeoticum and dicoccoides images. Due to the diversity of microscopes, cameras and chemical treatments that can influence images of phytolith slides, three types of data augmentation techniques have been implemented: rotation of the images at 45-degree angles, random colour and brightness jittering, and random blur/sharpen. The implemented workflow has resulted in an overall accuracy of 93.68% for phytolith genera, improving previous attempts. The algorithm has also demonstrated its potential to automatize the classification of phytoliths species with an overall accuracy of 100%. The open code and platforms employed to develop the algorithm assure the method's accessibility, reproducibility and reusability. •Deep learning automates identification and classification of multi-cell phytoliths.•Can be applied to digitalised slides and integrated into digital microscopes.•Can differentiate between phytolith genera but also species.•Presents an overall accuracy of 93% and analyses the whole slide.•Provides complementary metrics with new relevant information on phytoliths.